2014
DOI: 10.1017/s1751731114001645
|View full text |Cite
|
Sign up to set email alerts
|

The in ovo administration of l-trans pyrrolidine-2,4-dicarboxylic acid regulates small intestinal growth in chicks

Abstract: Glutamate, which is one of the most important contributors to oxidative metabolism in the intestinal mucosa, is mainly transported by the excitatory amino acids transporters (EAATs) that are expressed in enterocytes. The objective of this study was to evaluate the effects of in ovo administration of L-trans pyrrolidine-2,4-dicarboxylic acid (L-trans-PDC), a potent competitive inhibitor of glutamate uptake by EAATs, on the growth of the small intestine in chicks. Two series of experiments were conducted with ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Glu absorption is mainly mediated by EAAT3 in the nervous system [16], gastrointestinal tract [5, 17] and skeletal muscle [18]. Our previous studies revealed that EAAT3 is a marker of intestinal growth during embryonic development in chicks [7, 19] and pigeons [2022]. In addition, Glu deficiency or absorptive inhibition of EAAT3 decreased IPEC-1 cell proliferation [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glu absorption is mainly mediated by EAAT3 in the nervous system [16], gastrointestinal tract [5, 17] and skeletal muscle [18]. Our previous studies revealed that EAAT3 is a marker of intestinal growth during embryonic development in chicks [7, 19] and pigeons [2022]. In addition, Glu deficiency or absorptive inhibition of EAAT3 decreased IPEC-1 cell proliferation [6].…”
Section: Discussionmentioning
confidence: 99%
“…Studies with pigs, rats and mice demonstrate that the excitatory amino acid transporter 3 (EAAT3), encoded by solute carrier family 1 member 1 ( SLC1A1 ), is the predominant anionic amino acid transporter in the intestine [5]. In our previous studies, EAAT3 inhibition decreased pig intestinal epithelial cell (IPEC-1) proliferation [6] and intestinal growth in chick embryos [7]. Landeghem, et al .…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic growth in precocial birds has been widely investigated, for instance duck (Tangara et al, 2010), turkey (Stepińska et al, 2012), and chicken (Li et al, 2014). In contrast to precocial poultry, young pigeons, a typical representative of altricial birds, are feed with pigeon milk from the crop by parents for a few days.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient absorption, mediated by nutrient transporters, supports the growth of intestinal epithelial cells. Our previous studies have shown that the gene expression of SLC1A1 , SLC7A9 , and SLC15A1 in chicks [ 19 , 20 ] and SLC7A9 , SLC1A1, SLC43A2 , SLC15A1 , SLC9A2 , SLC9A3 , and SLC7A6 in pigeons positively correlates with the growth of embryonic intestines [ 21 , 22 ]. In addition, the inhibition of SLC1A1 decreased the proliferative activity of the IPEC-1 cells, as expected [ 23 ].…”
Section: Discussionmentioning
confidence: 99%